Extração e exportação de nutrientes pelo híbrido de mamona Savana: II – micronutrientes - Costa Crusciol, Carlos Alexandre [UNESP]; do Nascimento, Martha Santana; Fernandes, Adalton Mazetti [UNESP]; Zanotto, Maurício Dutra [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
Information about micronutrients extraction and exportation by castor bean hybrids of short stature, and the periods of highest demand for each micronutrient, are most importance for correct management to fertilization. This study aimed to evaluate the micronutrients extraction and exportation by Savana hybrid castor bean, on season and out-of-season growing. The experiments were conducted during season of 2005/2006 and out-of-season of 2006 in an Oxisol. The experimental design was a randomized block with four replications. The plots were consisted by harvest times of plants, which were carried out at 17, 31, 45, 59, 73, 97 and 120 days after emergence (DAE) during the season and at 17, 31, 45, 59, 80; 100 and 120 DAE in the out-of-season. In both seasons the order of micronutrients extraction by hybrid Savanna is: Fe> Mn> Zn> B> Cu> Mo, but with larger amounts of season cultivation. The time of greatest Zn and Mo absorption during the season and the Fe in out-of-season occurs at 80 DAE, although the other micronutrients are absorbed at higher rates between 50 and 65 DAE. In season the yield, nutrients extraction and exportation from soil are higher than out-of-season, but the nutrients extraction and exportation per ton show less variation between growing seasons. Fifty percent of zinc and 60% of Cu uptaken, on average, in out-of-season is exported with grains, but for the other micronutrients the proportion exported with grains is less than 40%.
Nutrients extraction and exportation by Savana castor bean hybrid: II - micronutrients
Keywords: Ricinus communis; mineral nutrition; absorption curves; absorption rates; yield